Determination of Filtration and Purification System for Flood Water Filter - Aini Kamarudin, Nurul; Khairul Amri Kamarudin, Mohd; Umar, Rosalan; Rahman Hassan, Abdul; Lananan, Fathurrahman; ., Sunardi (International Journal of Engineering and Technology, 2018)
Water is one of the basic needs which essential to life but cannot take it easy, it becomes more concern when a flood, there is plenty of dirty water than clean water, and the sources of the water are not approved to use. There are many kinds of waterborne pathogens which can donate diseases also death if not treating the water well before use. The treatment can be utilized based on the size of the microorganism. By identifying the size of the smallest bacteria will make easier to find the filtration based on the size of filter pores and other processes to ensure all the bacteria is removed and the water safe to use. Even there are many kinds of bacteria or microorganisms in the contaminated water, but the pathogens need to deal. The water will become clean and safe to use when the colour is clear and there is any pathogenic microorganism in there. This study is to ensure water is clean from pathogen after the flood water is filtered by know for sure the organismâ€™s size and to overcome the lack of clean water problem during the flood and others purpose.Â